Study on ultrasound observations in children with typhoid fever in a tertiary care hospital - Md., Zubair Ahamed; Belavadi, Gangadhar B. (International Journal of Contemporary Pediatrics, 2020)
Background: Enteric fever continues to be endemic in poor countries globally, although it has been eradicated from the developed nations due to their well-organized sanitation and protected water supply. The five Fs most concerned with spread of typhoid disease are fingers, food, fomites, flies, and feces. Enteric fever is predominantly caused by Salmonella typhi and next in frequency is Salmonella paratyphi. Very less literature is available on radiological manifestations of typhoid fever in children on the basis of age difference in India. Hence, a study was conducted to observe the radiological findings and to correlate with laboratory manifestations in typhoid fever. Objectives of the study was to observe the ultrasound abdomen changes in Typhoid fever at rural area. Methods: The current study was conducted at Department of pediatrics of Narayana Medical College Hospital, Nellore, Andhra Pradesh state in a period of one year. All patients presenting with fever having positive for Widal test were included. In total 50 patients were included and divided into 2 age groups, <5 years and >5years. The laboratory results and abdominal ultrasound were conducted in the two groups and compared. Results: Total 20 patients in <5 years age and 30 patients in >5 years were enrolled. Male to female ratio was 2:1 in both groups. Common laboratory findings showed 32 patients (64%) with Anemia, elevated liver enzymes in 40 patients (80%), and elevated ESR in 42 patients (84%). 45 patients have Splenomegaly and hepatomegaly with normal parenchymal echotexture. Gallbladder sludge and biliary sludge was seen in 6 patients. Thickened gall bladder in 34 patients (68%) was observed. Bowel wall thickening seen in 32 patients (64%). mesenteric lymphadenopathy in 36 patients (68%) observed. All were recovered by treatment. Conclusions: On ultrasound, splenomegaly, hepatomegaly, and thick-walled gallbladder were observed in most of the childrens with typhoid fever. Therefore, ultrasound can also be used as supportive diagnose along with laboratory parameters due to it is a non-invasive and economical tool of diagnosing typhoid.